Die Unsichtbaren - Kahlmeyer, Benjamin; Kahlmeyer, Benjamin (Academic Video Online, 2014)
Europe is in the grip of an immigration crisis: people from Africa, the Middle East, and elsewhere are arriving in ever greater numbers as they flee war, oppression, and a lack of opportunity. Germany receives more asylum seekers than any other European country. The Invisibles presents the human face of the immigration crisis, following four migrants from Syria, Kenya and Cameroon as they wade through Germany's rigorous immigration process and await the final verdict on their applications for asylum. At the initial registration center in EisenhÃơttenstadt, the men bond with fellow asylum seekers and attempt to stave off boredom and growing anxiety about their future. For all four, Germany is their only option. There is no 'Plan B'#x9D; should their applications be rejected. Some face life threatening circumstances if they are deported back to their home country. All are aware of how slim their chances, as Germany accepts only about 25% of asylum applicants. Without narration, the camera lingers to convey the uneasy stasis their lives have now become during this long and uncertain transitional period. During their three month wait in Germany, they are transferred to other camps or centers. As one man puts it while surveying his new location, 'Is this our home or our new cage?'